ANALISIS YURIDIS TERHADAP PERJANJIAN TERTUTUP YANG DILAKUKAN OLEH PT. PELABUHAN INDONESIA II (PERSERO) DI PELABUHAN TELUK BAYUR SUMATERA BARAT (STUDI KASUS TERHADAP PUTUSAN PERKARA NOMOR 02/KPPU-I/2013) - Puspariti, Cesi; b, Maryati; Hendra, Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
An enclosed field of business law is the field of anti- monopoly and antitrust (competition). Law defines a monopoly as a mastery and or marketing of goods or the use of certain services by 1 businesses or one group of business actors. Thus , according to the legislation of the Anti- Monopoly with monopolistic practices are intended as a concentration of economic power by one or more businesses that resulted in control of the production and or marketing of goods and or services giving rise to an unhealthy competition and can harm the public interest . Based on the Commission 's decision No. 02 / KPPU - 01 / 2013 Teluk Bayur otherwise violate Article 15, Paragraph 2 of the Constitution of 1999 on Monopolistic Practices and Unfair Competition . Teluk Bayur decided violates the provisions of law for committing a closed agreement with the tenants in Teluk Bayur, which cause unfair competition among businesses that are unloading Teluk Bayur Ports , because they block the loading and unloading of other businesses.Keywords : tying agreement - PT. Pelabuhan Indonesia II (Persero) – Teluk Bayur Port - Putusan Perkara - Nomor 02/Kppu-1/2013